2008
DOI: 10.1111/j.1469-0691.2008.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of superantigenic toxin Vβ T-cell signatures produced during cases of staphylococcal toxic shock syndrome and septic shock

Abstract: Most clinical isolates of Staphylococcus aureus harbour genes encoding superantigenic toxins that bind the Vbeta domain of T-cells, but little information is available concerning superantigenic toxin production during staphylococcal toxic shock syndrome (TSS) and septic shock. This prospective study investigated 14 patients with staphylococcal TSS or septic shock; the toxin gene profile of each isolate was determined and flow-cytometry was used to identify the discriminant Vbeta signature (DVbetaS) of each sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…The first study included nine patients with Staphylococcus aureus septic shock (26), and no specific T-cell repertoire modifications were observed. In the second study, Unsinger et al (27) showed that after cecal ligation and puncture, mice presented with lymphopenia but that the TCR repertoire measured 21 days after cecal ligation and puncture was not skewed toward any Vβ type but resembled the repertoire found in normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…The first study included nine patients with Staphylococcus aureus septic shock (26), and no specific T-cell repertoire modifications were observed. In the second study, Unsinger et al (27) showed that after cecal ligation and puncture, mice presented with lymphopenia but that the TCR repertoire measured 21 days after cecal ligation and puncture was not skewed toward any Vβ type but resembled the repertoire found in normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few clinical studies have attempted to correlate shock and outcome with the presence of certain SEs in patients with S. aureus infections (17,28), the contribution of these toxins to outcome is still unclear. Recent papers have proposed the SEs are immunomodulators and that colonization with S. aureus strains that produce SEB may contribute to the pathogenesis of asthma, chronic rhinitis, and dermatitis (2,36,46,48,56).…”
mentioning
confidence: 99%
“…As SAgs are active at very low concentrations (less than 1 pg/ml) (44), which are barely detectable in vivo, SAg-related diseases might theoretically be identified by determining TCR V␤ specificities in vitro. For example, an expansion of V␤2 T cells on the one hand and of V␤3, -14, and -17 T cells on the other hand, which correspond to TSST-1 and SEB superantigenic activities, respectively, has been detected in patients with TSS (6,10,25,29). Such an approach would be particularly useful for investigating suspected SAg-related diseases, including some inflammatory disorders, Kawasaki disease, and atopy (11).…”
mentioning
confidence: 99%